Mutations of KIF14 cause primary microcephaly by impairing cytokinesis. Issue 4 (14th October 2017) - Moawia, Abubakar; Shaheen, Ranad; Rasool, Sajida; Waseem, Syeda Seema; Ewida, Nour; Budde, Birgit; Kawalia, Amit; Motameny, Susanne; Khan, Kamal; Fatima, Ambrin; Jameel, Muhammad; Ullah, Farid; et al.
Abstract : Objective: Autosomal recessive primary microcephaly (MCPH) is a rare condition characterized by a reduced cerebral cortex accompanied with intellectual disability. Mutations in 17 genes have been shown to cause this phenotype. Recently, mutations in CIT, encoding CRIK (citron rho‐interacting kinase)—a component of the central spindle matrix—were added. We aimed at identifying novel MCPH‐associated genes and exploring their functional role in pathogenesis. Methods: Linkage analysis and whole exome sequencing were performed in consanguineous and nonconsanguineous MCPH families to identify disease‐causing variants. Functional consequences were investigated by RNA studies and on the cellular level using immunofluorescence and microscopy. Results: We identified homozygous mutations in KIF14 (NM_014875.2;c.263T>A;pLeu88*, c.2480_2482delTTG; p.Val827del, and c.4071G>A;p.Gln1357=) as the likely cause in 3 MCPH families. Furthermore, in a patient presenting with a severe form of primary microcephaly and short stature, we identified compound heterozygous missense mutations in KIF14 (NM_014875.2;c.2545C>G;p.His849Asp and c.3662G>T;p.Gly1221Val). Three of the 5 identified mutations impaired splicing, and 2 resulted in a truncated protein. Intriguingly, Kif14 knockout mice also showed primary microcephaly. Human kinesin‐like protein KIF14, a microtubule motor protein, localizes at the midbody to finalize cytokinesis by interacting with CRIK. We found impaired localization of both KIF14 and CRIK at the midbody in patient‐derived fibroblasts. Furthermore, we observed a large number of binucleated and apoptotic cells—signs of failed cytokinesis that we also observed in experimentally KIF14‐depleted cells. Interpretation: Our data corroborate the role of an impaired cytokinesis in the etiology of primary and syndromic microcephaly, as has been proposed by recent findings on CIT mutations. Ann Neurol 2017;82:562–577